Pink Mold Rot on Unishiu Orange (Citrus unshiu Mac.) Caused by Trichothecium roseum (Pers.) Link ex Gray in Korea - Jin-Hyeuk Kwon; Dong-Wan Kang; Okhee Choi; Hong-Sik Shim (Research in Plant Disease, 2013)
In 2012, a pink mold rot was observed on unishiu orange (Citrus unshiu Mac.) fruits at the Wholesale Market for Agricultural Products, Jinju, Korea. The symptom on unishiu orange was a water-soaked lesion on the surface of fruit, which later on enlarged to form softened brown rot lesions. The diseased fruits were covered with pink-colored mold, consisting of conidia and conidiophores of the pathogen. Optimum temperature for mycelial growth was 25oC. Conidia were hyaline, smooth, 2-celled, and thick-walled conidia with truncate bases, ellipsoidal to pyriform, characteristically held together zig-zag chains and 12−26 × 8−12 μm in size. Conidiophore was erect, colorless, unbranched, and 4−5 μm wide. On the basis of mycological characteristics, pathogenicity test, and molecular analysis with complete ITS rDNA region, the causal fungus was identified as Trichothecium roseum (Pers.) Link ex Gray. This is the first report of pink mold rot caused by T. roseum on unishiu orange in Korea.